Blockchain-based Decentralized Authentication and Authorization for IoT Applications - Zangana, Dr. Hewa Majeed; Beitollahi , Hakem; Muhamad , Sabat Salih; Omar , Marwan; Mustafa, Firas Mahmood; Mohammed , Aquil Mirza; Wani , Sharyar; Li , Shuai (CV. Abhinaya Indo Group, 2025)
The rapid proliferation of Internet of Things (IoT) devices has introduced significant challenges in ensuring secure and efficient authentication and authorization mechanisms. Traditional centralized approaches are increasingly inadequate due to their single points of failure, scalability issues, and vulnerability to attacks. This paper explores a blockchain-based decentralized framework for authentication and authorization in IoT applications, leveraging the inherent security features of blockchain technology. The proposed solution employs smart contracts to automate and enforce access control policies, ensuring that IoT devices can securely interact without relying on a trusted third party. By integrating blockchain with IoT, this approach enhances data integrity, transparency, and auditability while mitigating common security risks associated with centralized systems. The paper provides a comprehensive analysis of the architecture, implementation details, and performance evaluation, demonstrating the feasibility and advantages of the proposed decentralized authentication and authorization scheme. Experimental results indicate improved security, scalability, and operational efficiency, positioning blockchain as a promising solution for secure IoT environments.